2019
DOI: 10.3390/antiox8120648
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Alpha-Lipoic Acid on Hypertension, Visceral Obesity, UCP-1 Expression and Oxidative Stress in Zucker Diabetic Fatty Rats

Abstract: Evidence suggests that oxidative stress plays a major role in the development of metabolic syndrome. This study aims to investigate whether α-lipoic acid (LA), a potent antioxidant, could exert beneficial outcomes in Zucker diabetic fatty (ZDF) rats. Male 6-week-old ZDF rats and their lean counterparts (ZL) were fed for six weeks with a standard diet or a chow diet supplemented with LA (1 g/kg feed). At 12 weeks of age, ZDF rats exhibited an increase in systolic blood pressure, epididymal fat weight per body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…MetS associated with obesity and can develop diabetes in some patients (McNeilly et al, 2011; Patel, Matnor, Iyer, & Brown, 2011). Likewise, other MetS conditions such as hypertension or dyslipidemia could be associated with diabetes status such as insulin resistance (El Midaoui, De Champlain, Sadi, Husain, & Fantus, 2007; El Midaoui, Fantus, Ait Boughrous, & Couture, 2019). Insulin resistance is considered a critical factor in the development of metabolic disorders (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MetS associated with obesity and can develop diabetes in some patients (McNeilly et al, 2011; Patel, Matnor, Iyer, & Brown, 2011). Likewise, other MetS conditions such as hypertension or dyslipidemia could be associated with diabetes status such as insulin resistance (El Midaoui, De Champlain, Sadi, Husain, & Fantus, 2007; El Midaoui, Fantus, Ait Boughrous, & Couture, 2019). Insulin resistance is considered a critical factor in the development of metabolic disorders (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that LA exerts anti-obesity effects by suppressing hypothalamic AMP-activated protein kinase activity followed by a reduction in food intake and an increase in energy expenditure [53,54]. Zucker diabetic fatty rats fed LA showed a decrease in epididymal fat weight per body weight ratio associated with an upregulation of epididymal uncoupled protein-1 that plays a key role in non-shivering thermogenesis [55].…”
Section: Discussionmentioning
confidence: 99%
“…In this case the anti-obesity effect of ALA could be a consequence of the increase in energy expenditure, especially as ALA stimulates both cellular glucose uptake [60][61][62] and ATP synthesis, being an important cofactor of mitochondrial pyruvate and ketoglutarate dehydrogenases [63,64]. Furthermore, several studies have noted that ALA activates skeletal muscle 5' adenosine monophosphate-activated protein kinase (AMPK), with a subsequent enhancement of fatty acid β-oxidation [25,65] and increases mitochondrial uncoupling protein (UCP)-1 expression in adipose tissue, which has an important role in non-shivering thermogenesis [24]. Therefore, it could be assumed that by these two combined mechanisms, ALA increases whole-body energy expenditure [66], stimulating weight loss or preventing weight gain, depending on the initial body weight at the moment of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its safety profile is well characterized [23] and its specific amphiphilic properties could allow for a better intra-cellular and extra-cellular distribution [22]. Consequently, multiple studies have reported the benefits of ALA treatment in metabolic syndrome (hyperglycemia, tissue insulin resistance and dyslipidemia) [17], hypertension [17,24] and obesity [25][26][27].…”
Section: Introductionmentioning
confidence: 99%